Impacts of Clean Energy Technologies on Water Resources - LI Kaituo; SHU Zhihai; WANG Haojie (Renmin Zhujiang)
With the growing global energy demand,clean energy has become crucial to a low-carbon society and sustainable development.Although clean energy holds significant advantages in aspects such as carbon emissions and environmental pollution,its development and utilization may still pose specific impacts on water resources.This paper primarily investigates the impacts of various types of clean energy (including hydro-energy,nuclear power,geothermal energy,biomass energy,solar energy,and wind energy) on water resources and their underlying causes and suggests potential solutions to these issues.It provides reference information for the development and application of technology,formulation and implementation of relevant policies,and promotion of environmental science and technology,aiming at the sustainable utilization of clean energy and water resources.Elucidating the impacts of clean energy on water resources and providing countermeasures can provide technical support for governments and businesses to achieve carbon peak,carbon neutrality,and other objectives.